2018
DOI: 10.5005/jp-journals-10024-2346
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Cytotoxicity of Root Canal Sealers on Cultured Human Periodontal Fibroblasts:In vitroStudy

Abstract: Having knowledge of the cytotoxicity of various sealers will help in increasing patient's comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…When comparing MTT methodology with others, previous studies have demonstrated that MTT prevent over or underestimation of cell viability during cytotoxicity evaluation, thus considered reliable. [34] As well as, MTT has also been used in previous studies to determine cytotoxic effects caused by different dental materials on HGF, [35] human periodontal ligament fibroblast cells, [36] and in mouse fibroblast cells. [37] Likewise, previous studies have evaluated cell viability of TiO 2 N using MTT method on human cells.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing MTT methodology with others, previous studies have demonstrated that MTT prevent over or underestimation of cell viability during cytotoxicity evaluation, thus considered reliable. [34] As well as, MTT has also been used in previous studies to determine cytotoxic effects caused by different dental materials on HGF, [35] human periodontal ligament fibroblast cells, [36] and in mouse fibroblast cells. [37] Likewise, previous studies have evaluated cell viability of TiO 2 N using MTT method on human cells.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, in vitro cytotoxicity was evaluated using the CCK-8 assay. HPDLFs represent an appropriate model for testing cytotoxicity of root canal medicaments 44 , 45 . Moreover, the normal diploid cells (e.g.…”
Section: Discussionmentioning
confidence: 99%